Dinarzad's children : an anthology of contemporary Arab American fiction - Kaldas, Pauline, 1961-; Mattawa, Khaled; Darraj, Susan Muaddi; Kaldas, Pauline, 1961-; Alameddine, Rabih; Mustafah, Sahar; Ward, Patricia Sarrafian, 1969-; Geha, Joseph; Munn, May Mansoor; Kahf, Mohja, 1967-; Hage, Rawi; Melhem, D. H.; et al. (University of Arkansas Press, 2009)
Pauline Kaldas is assistant professor of English and creative writing at Hollins University. She was born in Egypt and immigrated to the United States in 1969. She is the author of Letters from Cairo and Egyptian Compass. Khaled Mattawa, a 2014 MacArthur fellow, is associate professor Department of English Language and Literature at the University of Michigan, Ann Arbor. He was born in Libya and immigrated to the United States in 1979. He is the author of four books of poetry and a number of translations of contemporary Arab poetry. His work has won two Pushcart Prizes, a Guggenheim Fellowship,